Pelatihan Penyelenggaraan Jenazah Bagi Masyarakat Awam di Desa Laikaaha Kec. Ranomeeto Kab. Konawe Selatan Sulawesi Tenggara - Muallimah; Yusuf (Amaliah: Jurnal Pengabdian Masyarakat, 2017)
The organization of the corpse is a responsibility for every Muslim although his responsibility are not up to farhu ‘ain but fardhu kifayah. The person who did it gets a very unusual reward beside Allah Subhanahu wa Ta’ala. Vice versa if no one who want to carry out these activities then all the Muslims who are in the place are sin. So it is necessary to improve the understanding of the community in the village of Laikaaha in conducting the corpse in the form of community service grant Muhammadiyah University of Kendari. Therefore it takes a team or a group that is really able to carry out the activity, so that the communities no longer take energy from outside their village to take care of the corpse if there are people who died Laikaaha community. So the result has been formed a team capable of taking care of the body in Laikaaha village.